2011
DOI: 10.1111/j.1747-0285.2011.01124.x
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses and Pharmacological Evaluations of Novel N‐Substituted Bicyclo‐Heptane‐2‐amines at N‐Methyl‐d‐Aspartate Receptors

Abstract: Several novel norcamphor (bicycloheptane) based compounds were designed and synthesized as noncompetitive NMDA receptor antagonists at the Phencyclidine (PCP) binding sites. The heterocyclic ring was also varied to examine piperidine, pyrrolidine and morpholine groups. We examined pharmacological activities of these compounds in vitro (binding studies) and in vivo (MES test). Pharmacological evaluations revealed one of the compounds, 5a, to be a good lead, exhibiting moderate binding at NMDA receptors (IC50 = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Target compounds 5a – f were synthesized as described in our previous publication [ 17 ]. Briefly, an appropriately substituted bromobenzene was reacted with magnesium to give a Grignard reagent which was reacted with commercially available norcamphor to give the desired alcohol.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Target compounds 5a – f were synthesized as described in our previous publication [ 17 ]. Briefly, an appropriately substituted bromobenzene was reacted with magnesium to give a Grignard reagent which was reacted with commercially available norcamphor to give the desired alcohol.…”
Section: Resultsmentioning
confidence: 99%
“…Treatment with memantine or any of the test compounds resulted in a concentration dependent decline in numbers of viable cells at higher than 100 µM concentration. Our previous studies have indicated that compound 5a exhibits the highest affinity for NMDA receptor and greatest degree of protection from MES (maximal electroshock)-induced neural damage in rodents [ 17 ]. It is known, that under therapeutic conditions in patients, the serum level of memantine is about 1 µM [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The observations described in this and similar works are leading to new interests by us and others in the possibilities of discovery of NMDAR antagonists with reduced toxicities as potential compounds for treatment of depression and other CNS disorders [ 58 ].…”
Section: Nmda Receptor Antagonistsmentioning
confidence: 99%